Evaluating Biometric Traits for Selecting Elite Trees in Acacia nilotica (Var. Indica) Based on Progeny Trials in Tropical India - Jayaprakash, J.; Rathore, A. C.; Raizada, A.; Singh, Charan; Dasthagir, M. G. (Indian Forester, 2010)
To improve the growth and yield of Acacia nilotica Linn. (Babul) a study was conducted using genetically superior elite trees. The study revealed that the selected traits viz. plant height, basal diameter, number of branches and volume were highly significant which indicate higher variability among half-sibs. Further, regression analysis revealed that the half-sibs of TNPKM1 and KRKL2 are best and may be utilized for future breeding programmes. Overall study implies that the traits like plant height, basal diameter and number of branches have maximum influence on volume, hence the traits will be useful in selecting Acacia nilotica trees for agroforestry development programmes.